Case report: Intraretinal hyperflow microinfiltration lesions on swept-source optical coherence tomography angiography as a potential biomarker of primary vitreoretinal lymphoma - Xu, Zhangxing; Bai, Haixia; Liu, Xin; Shen, Junhui; Su, Yongchao; Wang, Yao (Frontiers in Medicine, 2024)
Primary vitreoretinal lymphoma (PVRL) is often associated with central nervous system involvement, contributing to a heightened mortality rate, thus imaging features that are characteristic enough to be potential biomarkers of PVRL are important, either in diagnosis or in assessment of disease activity. This report details the case of a 68-year-old male who presented with blurred vision in both eyes persisting for 2 months. Fundus examination demonstrated vitreous opacity and multiple subretinal yellow nodular lesions of varying sizes in the peripheral fundus of both eyes. Multiple vertical hyperreflective lesions in the neural retina of posterior pole, indistinct outer retina borders in the fovea, and hyperreflective lesions in the sub-retinal pigment epithelium (RPE) space of the peripheral retina were demonstrated on swept-source optical coherence tomography (SS-OCT) of the left eye. Hyperflow signals corresponding to the vertical hyperreflective lesions were detected on swept-source optical coherence tomography angiography (SS-OCTA) images of retinal deep capillary plexus (DCP) layer. Notably, the hyperflow signals, precisely located around retinal vessels from the nerve fiber layer to the outer plexiform layer, were postulated to stem from the dilation of infiltrated retinal vessels. Vitreous pathological results of the left eye confirmed the diagnosis of PVRL. Treatments with intravitreal methotrexate injections led to a marked improvement of best-corrected visual acuity (BCVA) and regression of the hyperflow microinfiltration lesions demonstrated on SS-OCTA. In conclusion, SS-OCTA effectively delineated the vertical hyperreflective lesions and corresponding hyperflow signals in the posterior pole macular region of a patient with PVRL. These lesions significantly diminished following intravitreal methotrexate injections. We speculated that the specific hyperflow signals on SS-OCTA could act as a potential biomarker of PVRL, and SS-OCTA holds promise in facilitating early diagnosis and monitoring therapeutic responses in PVRL cases.